Cyber war the next threat to national security and what to do about it - Clarke, Richard A. (Richard Alan) 1951-; Knake, Robert K. (HarperCollins Publishers, 2010)
Traces the rise of the cyber age and profiles the characters at its epicenter, including criminals, spies, soldiers, and hackers. This title outlines how our national security has already been compromised, and what America stands to lose if we continue to follow policies that block our ability to defend ourselves against a cyber attack